2020
DOI: 10.1038/s41598-020-74544-5
|View full text |Cite
|
Sign up to set email alerts
|

TAP2, a peptide antagonist of Toll-like receptor 4, attenuates pain and cartilage degradation in a monoiodoacetate-induced arthritis rat model

Abstract: Because inflammation in osteoarthritis (OA) is related to the Toll-like receptor 4 (TLR4) signaling cascades, TLR4 is a reasonable target for developing therapeutics for OA. Thus, we investigated whether TAP2, a peptide antagonist of TLR4, reduces the monoiodoacetate (MIA)-induced arthritic pain and cartilage degradation in rats. TLR4 expression of human OA chondrocytes and synoviocytes and the knee joint tissue of MIA-induced arthritis were evaluated. MIA-induced arthritic model using Sprague–Dawley rats (6 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
7
1
Order By: Relevance
“… 59 In agreement, we observed no improvement in the histopathology of the joint of OA animals receiving the TLR4 antagonist, despite the reduction in nociception and in neuronal injury, which reinforces the possible distinct actions of the TLR4 pathway. This is in contrast with the study of Park et al 11 which showed a reduction of cartilage degradation upon TAP2 administration. However, since inflammatory events involving TLR4 are complex, the two antagonists might produce different effects in the downstream pathway.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“… 59 In agreement, we observed no improvement in the histopathology of the joint of OA animals receiving the TLR4 antagonist, despite the reduction in nociception and in neuronal injury, which reinforces the possible distinct actions of the TLR4 pathway. This is in contrast with the study of Park et al 11 which showed a reduction of cartilage degradation upon TAP2 administration. However, since inflammatory events involving TLR4 are complex, the two antagonists might produce different effects in the downstream pathway.…”
Section: Discussioncontrasting
confidence: 99%
“…Being the TLR4 responsible for their recognition and for the expression of costimulatory molecules on antigen presenting cells, 42 , 43 TLR4-A1 could be blocking this immune-mediated response, possibly by preventing the activation of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) signaling pathway and the production of TNF-α and IL-1β at the joint, which will lead to a reduction in the excitability of primary afferent neurons and to a reduction of movement-related nociception. 44 Park et al 11 have also recently showed that intra-articular administration of TAP2, a peptide antagonist of TLR4, suppressed the expression of pro-inflammatory cytokines at the joint of OA animals and also reduced the secondary mechanical allodynia. ATF-3, an adaptive response gene induced by a variety of stress signals, 45 is not expressed in most healthy intact neurons, but its expression is induced following nerve injury, 46 being associated with neuroprotective and regenerative effects in the peripheral nervous system.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The blockade of IL-1 receptor is used to treat rheumatoid arthritis (Mertens & Singh, 2009), gout (Pascart & Richette, 2017) and crystal-induced arthritis (Aouba et al, 2015). Although TLR4 has been proposed as a therapeutic target for osteoarthritis and other arthritides (H. Park et al, 2020), a viable TLR4 inhibitor has yet to be found.…”
Section: Discussionmentioning
confidence: 99%
“…The blockade of IL‐1 receptor is used to treat rheumatoid arthritis (Mertens & Singh, 2009 ), gout (Pascart & Richette, 2017 ) and crystal‐induced arthritis (Aouba et al, 2015 ). Although TLR4 has been proposed as a therapeutic target for osteoarthritis and other arthritides (H. Park et al, 2020 ), a viable TLR4 inhibitor has yet to be found. Considering this, we determined whether amitriptyline, a drug that binds to TLR4 in mouse microglial cells (Hutchinson et al, 2010 ), could be repurposed as a TLR4 blocking agent to inhibit articular innate immune responses.…”
Section: Discussionmentioning
confidence: 99%